Edukasi dan Pendampingan Sertifikasi Halal Gratis (SEHATI) dengan Skema Self Declare bagi Pelaku UMKM Sumenep - Hanifah, Luluk; Putri, Filda Felisa (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
The development of Micro, Small and Medium Enterprises (MSMEs) requires legality and halal certification to ensure safety and compliance with regulations. This service activity was carried out to increase awareness and facilitate MSME owners in Sumenep, in obtaining a Business Identification Number (NIB) and halal certification through the Sehati Program based on self-declare. Service activities go through several stages, starting from surveying MSME data collection, socializing the importance of legality and halal certification, direct assistance in making NIB and assisting the halal certification process. The results of this service activity show an increase in understanding and awareness among MSME owners in Sumenep about the importance of legality and halal certification. And some MSMEs managed to get NIB and and get a halal certificate issued by BPJPH. This program has succeeded in increasing awareness, understanding and legality of MSMEs which ultimately supports the growth and sustainability of their businesses. As well as improving the quality and competitiveness of MSMEs at the local and national levels.